2017
DOI: 10.1002/pen.24768
|View full text |Cite
|
Sign up to set email alerts
|

Influence of α‐tocopherol/MCM‐41 assembly on physical and antioxidant release properties of low‐density polyethylene antioxidant active films

Abstract: α‐Tocopherol, usually used as an antioxidant in the packaging industry, was loaded into inner pore channels of Mobil composition of matter NO.41(MCM‐41) mesoporous silica material to control its release from packaging materials into fatty food simulant. Different amount of α‐tocopherol/MCM‐41 assembly were coextruded with low‐density polyethylene (LDPE) granulates to prepare antioxidant active films by flat extrusion. The influence of the assembly addition amounts on the properties of LDPE films including phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…It can be seen from these results that the values of the melting temperatures of LDPE/α‐tocopherol/MCM‐41 films stay constant at around 108°C with different mesopore sizes and morphologies of mesoporous materials incorporated, which means that these two factors have negligible influence on thermal properties of controlled release films. According to a previous study, 14 the melting temperatures of controlled release films are nearly the same as those of pure LDPE. Similar results have been found in other researches: Olmos et al found that silica nanoparticles with various addition amounts did not obviously influence melting temperature of LDPE 34 .…”
Section: Resultsmentioning
confidence: 52%
See 4 more Smart Citations
“…It can be seen from these results that the values of the melting temperatures of LDPE/α‐tocopherol/MCM‐41 films stay constant at around 108°C with different mesopore sizes and morphologies of mesoporous materials incorporated, which means that these two factors have negligible influence on thermal properties of controlled release films. According to a previous study, 14 the melting temperatures of controlled release films are nearly the same as those of pure LDPE. Similar results have been found in other researches: Olmos et al found that silica nanoparticles with various addition amounts did not obviously influence melting temperature of LDPE 34 .…”
Section: Resultsmentioning
confidence: 52%
“…Tensile strength and elongation of controlled release films are shown in Table 3. It can be found that, as compared with tensile properties of LDPE films, 14 these properties are improved by incorporating with controlled release assemblies. It can also be seen that tensile strength and Young modulus increase slightly from L1 to L4, which may, on the one hand, be attributed to the increase of crystallinity of these samples; on the other hand, this may be due to the increase of pore size from M1 to M4 as reported by Wang et al 40 Specifically, LDPE chain may be introduced in the mesopores of silica materials during film making process, and the chain in the larger pores can extend more easily along the channels to the openings enhancing interactions between polymeric matrix and the assemblies, thus leading to increasing tensile strength of samples from L1 to L4 films.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations